2018
DOI: 10.3390/polym11010025
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Analysis on the Effect of Antioxidants on the Thermal-Oxidative Stability of Commercial Mass- and Emulsion-Polymerized ABS

Abstract: In the present work, statistical analysis (16 processing conditions and 2 virgin unmodified samples) is performed to study the influence of antioxidants (AOs) during acrylonitrile-butadiene-styrene terpolymer (ABS) melt-blending (220 °C) on the degradation of the polybutadiene (PB) rich phase, the oxidation onset temperature (OOT), the oxidation peak temperature (OP), and the yellowing index (YI). Predictive equations are constructed, with a focus on three commercial AOs (two primary: Irganox 1076 and 245; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 24 publications
3
38
0
Order By: Relevance
“…All the absorbance results were normalized considering the maximum absorbance observed for the nitrile group (CN) at 2237 cm −1 . This absorption band was chosen since the CN group is expected to be stable after aging and recycling steps [3,[18][19][20]. Both the unexposed and exposed to UV radiation sides of the aged samples were analyzed.…”
Section: Chemical Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…All the absorbance results were normalized considering the maximum absorbance observed for the nitrile group (CN) at 2237 cm −1 . This absorption band was chosen since the CN group is expected to be stable after aging and recycling steps [3,[18][19][20]. Both the unexposed and exposed to UV radiation sides of the aged samples were analyzed.…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…The carbonyl (CO, ca. 1730 cm −1 ), the 1,4-butadiene (1,4BD, 966 cm −1 ), and the nitrile (CN, 2237 cm −1 ) absorption peaks were evaluated using the absorption ratios CO/CN and 1,4BD/CN as defined by the Equations (1) and (2), respectively [20].…”
Section: Chemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The yellowing index (YI) was obtained by the International Commission on illumination (CIE) tristimulus values X, Y and Z according to the CIELAB color system [37]. The YI was determined according to Equation (4) [22]:…”
Section: Color Measurementsmentioning
confidence: 99%
“…Some people chose traditional additives to improve heat resistance. For example, Fiorio's group found that the addition of primary antioxidants in ABS increases the thermal-oxidative stability, whereas the secondary antioxidants only increase the oxidation peak temperature [22]. Others have chosen new types of additives.…”
Section: Introductionmentioning
confidence: 99%